2021
DOI: 10.1002/bse.2936
|View full text |Cite
|
Sign up to set email alerts
|

A natural resource and institutional theory‐based view of green‐lean‐six sigma drivers for environmental management

Abstract: Green-lean-six sigma (GLSS) is an evolving strategy that can be applied in the manufacturing context to address pressing environmental issues. However, due to a lack of research in this area, investigating the motivations behind GLSS implementation is crucial to develop a deeper understanding of factors that shape the overall environmental management strategy of a firm. Drawing on the natural-resource-based view and institutional theory, we explore the GLSS drivers and compare developed and developing country … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 100 publications
(143 reference statements)
2
35
0
Order By: Relevance
“…Although both companies have implemented an EMS (ISO 14001), the findings revealed that Delta-flex is more concerned with environmental certifications such as ISO 50001 and the WWF green office diploma. These findings can be attributed to either increasing environmental awareness of manufacturing organizations in emerging economies to minimize emissions generated from their production operations (Massoud et al, 2011) or their international customers' requirements (Farrukh et al, 2021b).…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although both companies have implemented an EMS (ISO 14001), the findings revealed that Delta-flex is more concerned with environmental certifications such as ISO 50001 and the WWF green office diploma. These findings can be attributed to either increasing environmental awareness of manufacturing organizations in emerging economies to minimize emissions generated from their production operations (Massoud et al, 2011) or their international customers' requirements (Farrukh et al, 2021b).…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…These findings can be attributed to either increasing environmental awareness of manufacturing organizations in emerging economies to minimize emissions generated from their production operations (Massoud et al. , 2011) or their international customers' requirements (Farrukh et al. , 2021b).…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proactive firms are increasingly focusing on developing sustainable products and services as well as making their business operations more environmentally and socially friendly to cater to the growing needs of a wide range of stakeholders. Increasingly, firms are adopting Industry 4.0 and smart manufacturing technologies as well as cutting-edge information and communication technologiescloud computing and cognitive computing, radio-frequency identification (RFID), green lean six sigma (GLSS) approach, cyber-physical systems (CSP), digital sensors, artificial intelligence (AI), blockchain technology, 3D printing, machine learning, Internet of things (IoT), robotics and big data and analyticsto achieve sustainable outcomes (Allam & Dhunny, 2019;Alves, Galina, & Dobelin, 2018Dantas et al, 2020Farrukh, Mathrani, & Sajjad, 2021;Malik & Raziq, 2022;Sarkis, Cohen, Dewick, & Schr€ oder, 2020;Saunila, Nasiri, Ukko, & Rantala, 2019;Tjoa & Tjoa, 2016;Wu, Guo, Huang, Liu, & Xiang, 2018).…”
Section: Introductionmentioning
confidence: 99%